The game in numerical inferiority situations - de Dios Roman Seco, J. (2008)
For many years, the analysis carried out by experts on the greatest professional handball competitions and events (Olympic Games, World Championships, and European Championships) has highlighted the importance of the game in numerical inferiority situations, both offensive and defensive. Since the first stages in the history of the game some of the situations in handball that related to 2- minute suspensions have been thoroughly studied, especially those related to offensive play in superiority (6:5), and analysed scrupulously by all handball schools. Over these last years the basis for improving the defensive game in inferiority (5:6) had been deeply systemised and rigorously designed leading to noticeable results and new formulas. Analysing the results of the recent European Championship in Norway 2008, the importance of an effective game and its significance regarding the final result in 5:6 situations is confirmed.